Measuring Freedom at the Tip of the Gavel: Constitutional Implications of the 2026 National Criminal Code on Freedom of Expression and Civil Rights in Indonesia - Zainal Fanani; Misbachul Munir (VRISPRAAK : International Journal of Law, 2026)
The enactment of Indonesia's new National Criminal Code (KUHP) in 2026 marks a significant milestone in the nation's legal history, yet it raises profound constitutional questions regarding the protection of freedom of expression and civil rights. This article examines the constitutional implications of the new KUHP by analyzing the tension between constitutional guarantees under Articles 28E and 28F of the 1945 Constitution and the substantive provisions of the Criminal Code that regulate defamation, blasphemy, and public order offenses. Based on a comprehensive literature review of fifty relevant studies, this article finds that while the Constitutional Court has played a pivotal role in reviewing the constitutionality of various provisions—striking down articles on contempt against the president while upholding blasphemy laws—significant ambiguities persist. Vague statutory formulations lacking the lex certa principle enable selective prosecution and disproportionately affect religious minorities, dissenters, and critical voices. Press freedom remains fragile due to overlapping legal regimes between the Press Law, the KUHP, and the Electronic Information and Transactions (ITE) Law, compounded by the rise of Strategic Lawsuits Against Public Participation (SLAPPs). Comparative analysis reveals that Indonesia lags behind countries such as Canada and Ireland in establishing clear public interest defenses and precise standards for restricting speech. This article identifies critical research gaps, particularly concerning public interest defenses and mechanisms for protecting minority voices. It concludes that the constitutional implications of the new KUHP hinge on resolving statutory ambiguities, strengthening judicial interpretations that prioritize human rights, and developing robust safeguards against arbitrary enforcement. Without these measures, the new Criminal Code risks becoming an instrument that stifles the very freedoms the Constitution seeks to protect.